2004
DOI: 10.1590/s0034-70942004000100005
|View full text |Cite
|
Sign up to set email alerts
|

Volume gástrico residual e risco de aspiração pulmonar em crianças com refluxo gastroesofágico: estudo comparativo

Abstract: Children with gastroesophageal reflux were not at increased risk for pulmonary aspiration, as compared to children without reflux. Therefore, its prophylaxis would not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…For this reason, those patients were excluded from the abbreviation of preoperative fasting protocol. However, at least in children who ingested clear liquids two hours before surgery, residual gastric volume was not increased in patients with gastroesophageal reflux 13 . Recent studies indicate that the use of a carbohydrate-rich liquid solution increases patient satisfaction, decreases irritability and the incidence of vomiting, increases the pH, improves gastric emptying, and reduces the organic response to surgical stress [14][15][16] .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…For this reason, those patients were excluded from the abbreviation of preoperative fasting protocol. However, at least in children who ingested clear liquids two hours before surgery, residual gastric volume was not increased in patients with gastroesophageal reflux 13 . Recent studies indicate that the use of a carbohydrate-rich liquid solution increases patient satisfaction, decreases irritability and the incidence of vomiting, increases the pH, improves gastric emptying, and reduces the organic response to surgical stress [14][15][16] .…”
Section: Discussionmentioning
confidence: 89%
“…This was probably due to the time necessary for the combined anesthetic technique. Studies have demonstrated that prolonged fasting results in greater residual gastric volume with more acid pH, while ingestion of clear fluids up to two hours before the procedure decreases the residual volume and increases the pH [12][13][14] . Besides, prolonged preoperative fasting is not only uncomfortable and unnecessary, but it can also be harmful by potentiating or perpetuating the organic response to trauma 1,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence Summary: There were eight retrospective/observational studies, and one RCT (Table 13). 49–57 The studies were generally small, with a sample size range of 6 to 108. There was significant heterogeneity in the ages of the studied participants, and many studies recruited patients from a wide age range.…”
Section: Comorbidity Medications and Prematuritymentioning
confidence: 99%